School absenteeism among children and adolescents aged 6–19 years with sickle cell disease in Uganda: A comparative cross-sectional study - Juliane Peninah Nattimba; Sabrina Bakeera-Kitaka; Joseph Rujumba; Ruth Namazzi; Ivan Segawa; Kizza Lubega; Alphonse Taban; Edison Mworozi; Phillip Kasirye; Deogratias Munube; Grace Ndeezi; Sarah Kiguli; et al. (PLoS ONE, 2026)
Introduction Sickle cell disease (SCD) contributes substantially to school absenteeism due to recurrent pain, infections, and frequent hospital visits that interrupt learning and long-term academic progress. In Uganda, where the SCD burden is high, the extent and drivers of absenteeism are not well documented, limiting the development of supportive school health strategies. This study assessed the prevalence and associated factors of absenteeism among children and adolescents with SCD to inform education and health policy. Methods A comparative cross-sectional study was conducted at Mulago National Referral Hospital’s Sickle Cell Clinic in Kampala, Uganda, from 18 July to 03 November 2024. Children aged 6–19 years with SCD and their siblings or peers were consecutively enrolled. Chronic absenteeism: missing ≥10% of expected school days in the previous term (~89 days), was the primary outcome. Sociodemographic, school-related, and clinical data were collected through structured interviews and medical record review. Chi-square and Wilcoxon rank-sum tests were used to compare participant characteristics, while logistic regression identified factors associated with chronic absenteeism, generating odds ratios (ORs) and 95% confidence intervals (CIs). Results A total of 358 participants were enrolled (179 with SCD and 179 peers). Children with SCD missed a median of 5 school days per term (interquartile range [IQR]: 2–10), compared with 0 days (IQR: 0–3) among peers (p < 0.001). Chronic absenteeism affected 33% of children with SCD versus 6% of peers (OR 7.3, 95% CI: 3.7–14.4). In multivariable analysis, class repetition (adjusted OR [aOR] 2.5, 95% CI: 1.1–5.9) and hospital admissions (aOR 3.6, 95% CI: 1.9–6.8) were significantly associated with absenteeism. Conclusions Learners with SCD experienced significantly high rates of absenteeism compared to their peers, with one-third chronically absent. Frequent hospital admissions and prior class repetition were strongly associated, highlighting the need for integrated health-education strategies to enhance attendance and academic outcomes.